THE CORRELATION BETWEEN STUDENTS’ GRAMMATICAL MASTERY AND STUDENTS’ WRITING ACHIEVEMENT AT XI GRADE STUDENTS OF SMAN 1 TARAKAN ACADEMIC YEAR 2019/2020 - Betoni, Theodorus; Ulfaika, Romlah (Universitas Borneo Tarakan, 2020)
The objective of this research was to find out The correlation between students’ grammar mastery and students’ writing achievement at eleventh grade students of SMAN 1 Tarakan. Writing is one of the skills that required the users to master the grammar. The sample was taken from one of the 11 classes of eleventh grade students by used purposive sampling, to collect the data the researcher used Grammar Test and Writing Test. To analyse the data the researcher used Pearson Product Moment. This research used quantitative approach with correlation design, from the result of the research found that there was a fair correlation between students’ grammar mastery and students writing achievement. The result showed that between students’ grammatical mastery and students’ writing achievement obtained a significance value of 0.05 with a significant value of 0.0020.05 which means that there was a significant correlation between grammatical mastery and writing achievement, meanwhile for r test value r table with the correlation value was 0.5100.3388, the correlation of grammatical mastery and writing achievement was 0.510 which is a medium correlation between grammatical mastery and writing achievement. Based on the result of the research and discussion it can be concluded that there was a significant correlation between students’ grammatical mastery and students’ writing achievement at XI grade students of SMAN 1 Tarakan.